Visibility, accessibility and quality of Italian public health institutional websites (Italian Journal of Public Health, 2010)
Background: Since the large volume of health information available on the Web has the potential to improve health, Public Health institutions must represent a strong Internet presence with accessible and scientific information. The aims of the study were to verify the presence and visibility of Italian Institutions on the Web and to evaluate the accessibility and quality of the information provided.Methods: In a focus group setting, 21 keywords were generated, and launched in search-engines Google and MSN. Researchers noted the first 30 results found and determined the position of institutional websites. The accessibility of 303 Public Health websites was assessed in relation to the logo presence and web validation of XHTML, CSS and WAI indicators. Regarding the quality of information, the presence of the HONcode logo in the websites’ homepage was checked.Results: A high percentage of the keywords selected did not lead to any institutional website in the first three pages of Google (19.0%) and MSN (42.8%). Few institutional websites presented the logo indicator and a full web validation. Considering the XHTML indicator, only for 34.0% of the websites there was concordance between the logo presence/absence and results of direct validation, 50.2% for CSS. The quality level seemed to be extremely low.Conclusions:In order to achieve a larger visibility and guarantee accessibility, Public Health websites have to be correctly designed, edited and maintained. Common and strict European laws about health information on the Web have to be arranged, deeply monitored and carefully adjourned in order to guarantee and support the positive role of institutional websites.
Keywords: Public health; web; visibility; accessibility; quality